The systemic oral health connection: Biofilms. Issue 46 (18th November 2022) - Kurtzman, Gregori M.; Horowitz, Robert A.; Johnson, Richard; Prestiano, Ryan A.; Klein, Benjamin I.
Abstract : Frequently, periodontal health and it's associated oral biofilm has not been addressed in those patients who have systemic health issues, especially those who are not responding to medical treatment via their physician. Oral biofilm may be present in the periodontal sulcus in the absence of clinical disease of periodontal disease (bleeding on probing, gingival inflammation) and periodontal reaction is dependent on the patient's immune response to the associated bacterial and their byproducts. Increasing evidence has been emerging the past decade connecting oral biofilm with systemic conditions, either initiating them or complicating those medical conditions. The patient's health needs to be thought of as a whole-body system with connections that may originate in the oral cavity and have distant affects throughout the body. To maximize total health, a coordination in healthcare needs to be a symbiosis between the physician and dentist to eliminate the oral biofilm and aid in prevention of systemic disease or minimize those effects to improve the patient's overall health and quality of life. Various areas of systemic health have been associated with the bacteria and their byproducts in the oral biofilm. Those include cardiovascular disease, chronic kidney disease, diabetes, pulmonary disease, prostate cancer, colon cancer, pancreatic cancer, pre-term pregnancy, erectile dysfunction Alzheimer's disease and Rheumatoid arthritis. This article will discuss oral biofilm, its affects systemically and review the medical conditions associated with the oral systemic connection with an extensive review of the literature.